Proceedings of the 43rd International ACM SIGIR Conference on Research and Development in Information Retrieval 2020
DOI: 10.1145/3397271.3401164
|View full text |Cite
|
Sign up to set email alerts
|

Web-to-Voice Transfer for Product Recommendation on Voice

Abstract: While product recommendation algorithms on the Web are wellsupported by a vast amount of interaction data, the same is not true on Voice. A promising approach to mitigate the issue is transfer learning, i.e., transferring the knowledge of customers' shopping behaviors learned from their shopping activities on the Web to Voice. Such a Web-to-Voice transfer is challenging due to customers' distinct shopping behaviors on Voice: customers are inclined to purchase more low-consideration products and are more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As a result, there is currently no available public dataset for research on VCRSs. Besides, another work [44], though involving voice-based recommendation, aims to transfer customers' shopping patterns from the web to the voice platform, thus being different from our goal of CRSs directly on voices.…”
Section: Do You Like Pink and Gray Style?mentioning
confidence: 99%
“…As a result, there is currently no available public dataset for research on VCRSs. Besides, another work [44], though involving voice-based recommendation, aims to transfer customers' shopping patterns from the web to the voice platform, thus being different from our goal of CRSs directly on voices.…”
Section: Do You Like Pink and Gray Style?mentioning
confidence: 99%
“…Kraus et al (2019) surveyed a focus group of e-commerce experts on their experiences in the voice and web commerce recommenders and found that convenience has a larger effect in the voice commerce. Zhang and Yang (2020) considered the shopping behaviors on vocal as distinct from visual when they designed a network-based recommender system, which include the tendency to consume more lowconsideration products and purchase repeatedly. However, the effects of the output modality of recommendation explanation on user experience have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%